ANALISIS KADAR FORMALIN PADA BUAH IMPOR YANG DIJUAL DI BEBERAPA PASAR SWALAYAN DI KOTA MEDAN TAHUN 2015 - martha elnist ramadhani; devi nuraini santi; indra chahaya (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Formalin is substance which is banned to be added in food according to the regulation of Indonesia Health Minister Number 1168/Health Minister/Regulation/X/1999 But many manufacturers still use formalin to make durable import fruits to maintain the freshness of fruit because importing fruits from the origin country to Indonesia needs long time. The objective of this research is to know how many formalin in import fruits which is sold in some supermarket in Medan This research is survey research in descriptive. The methode of the research is laboratory check of apple imports, grape imports, and orange imports by iodimetri titration. Based on laboratory result from import fruits, can be known that all number of sample from import fruits contain formalin. The highest Formalin content in Calmeria Grapes from America is 4,692 mg/ml, Fuji Apple from Japan is 4,552 mg/ml, and Red Delicious Apple from America is 4,412 mg/ml, and the lowest formalin is in Imperial Seed Orange from Australia is 1,610 mg/ml. It is suggested to government to tighten the controls of importing fruits in to country to prevent the coming fruits which have dangerous content like formalin. Suggested to BPOM to monitor, control, and educate about formalin using as added substance in food. It is suggested also to people to be selective in choosing import fruits to consume. Suggested for further research done by comparing the levels of formaldehyde in import fruits peeled with import fruits not peeled . And comparing the levels of formaldehyde in import fruits before washing with after washing . Key Word : Formalin, Import Fruits